Analisis Manajemen Risiko Pada Pekerjaan Bangunan Pelimpah (Spillway) Proyek Bendungan Bulango Ulu - Mohamad Alit Deu; Mohammad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
Many problems may arise during the execution of construction projects as a consequence of risks, and these problems may lead to substandard performance, substandard quality, and substandard work results. Knowing how risk management is applied to construction projects and what technical risk factors occur most frequently during the execution of work in the field are the main objectives of this study. The spillway construction of the Bulango Ulu dam project is the subject of this research, which aims to identify, analyze, and respond to potential risks. Consultants, supervision contractors, and construction management are the research subjects who measure risk variables and take preventive measures. Assessing risk variables through surveys and weighing the relative importance of various activities according to the Index of Relative Importance (IKR). After reviewing the data, we have identified five risk factor variables that significantly impact the Bulango Ulu dam spillway project. These factors include incorrect dimensioning (length, width, and height), incorrect time estimation, out-of-specification concrete quality, use of incorrect execution methods, and errors in reinforcement (iron dimensions, iron spacing, and iron quality).